Structural and functional investigation of the Small Ribosomal Subunit Biogenesis GTPase A (RsgA) from Pseudomonas aeruginosa. (2nd July 2019) - Rocchio, Serena; Santorelli, Daniele; Rinaldo, Serena; Franceschini, Mimma; Malatesta, Francesco; Imperi, Francesco; Federici, Luca; Travaglini‐Allocatelli, Carlo; Di Matteo, Adele
Abstract : The Small Ribosomal Subunit Biogenesis GTPase A (RsgA) is a bacterial assembly factor involved in the late stages of the 30S subunit maturation. It is a multidomain GTPase in which the central circularly permutated GTPase domain is flanked by an OB domain and a Zn‐binding domain. All three domains participate in the interaction with the 30S particle thus ensuring an efficient coupling between catalytic activity and biological function. In vivo studies suggested the relevance of rsgA in bacterial growth and cellular viability, but other pleiotropic roles of RsgA are also emerging. Here, we report the 3D structure of RsgA from Pseudomonas aeruginosa ( Pa RsgA) in the GDP‐bound form. We also report a biophysical and biochemical characterization of the protein in both the GDP‐bound and its nucleotide‐free form. In particular, we report a kinetic analysis of the RsgA binding to GTP and GDP. We found that Pa RsgA is able to bind both nucleotides with submicromolar affinity. The higher affinity towards GDP ( K D  = 0.011 μm ) with respect to GTP ( K D  = 0.16 μm ) is mainly ascribed to a smaller GDP dissociation rate. Our results confirm that Pa RsgA, like most other GTPases, has a weak intrinsic enzymatic activity ( k CAT  = 0.058 min −1 ). Finally, the biological role of RsgA in P. aeruginosa was investigated, allowing us to conclude that rsgA is dispensable for P. aeruginosa growth but important for drug resistance and virulence in an animal infection model. Databases: Coordinates and structure factors for the protein structure described in this manuscript have been deposited in the Protein Data Bank (https://www.rcsb.org ) with the accession code 6H4D . Abstract : RsgA is a GTPase assisting the maturation of the ribosomal small subunit. We report the crystal structure of the protein from Pseudomonas aeruginosa together with its functional characterization, showing that it has a high affinity for nucleotides and weak intrinsic enzymatic activity. We also show that the protein is important for drug resistance and virulence in an animal model.